(untitled) (Research, Society and Development, 2021)
This article will investigate the new contemporary theories of social movements, without losing sight of the debate on classical theories, locating their historical emergence, central ideas and the theory of new social movements. It is assumed that social movements, from the linked theoretical school, address key issues in modernity with an economic, political and social bias. Therefore, it was adopted as a qualitative methodology, through a literature review.